Use of polygenic risk scores to select screening intervals after negative findings from colonoscopy - Guo, Feng; Weigl, Korbinian; Carr, Prudence R.; Heisser, Thomas; Jansen, Lina; Knebel, Phillip; Chang-Claude, Jenny; Hoffmeister, Michael; Brenner, Hermann (Clinical gastroenterology and hepatology, 2020)
Background & Aims - Polygenic risk scores (PRSs) could help to define starting ages for colorectal cancer (CRC) screening. However, the role of PRS in determining the length of screening interval after negative findings from colonoscopies is unclear. We aimed to evaluate CRC risk according to PRS and time since last negative colonoscopy. - Methods - We collected data from 3827 cases and 2641 CRC-free controls in a population-based case-control study in Germany. We constructed a polygenic risk scoring system, based on 90 single-nucleotide polymorphisms, associated with risk of CRC in people of European descent. Participants were classified as having low, medium, or high genetic risk according to tertiles of PRSs among controls. Multiple logistic regression models were used to assess CRC risk according to PRS and time since last negative colonoscopy. - Results - Compared to individuals without colonoscopy in the low PRS category, a 42%-85% lower risk of CRC was observed for individuals who had a negative finding from colonoscopy within 10 years. Beyond 10 years after a negative finding from colonoscopy, significantly lower risk only persisted for the low and medium PRS groups, but not for the high PRS group. Adjusted odds ratios were 0.44 (95% CI, 0.29-0.68), 0.51 (95% CI, 0.34-0.77), and 0.85 (95% CI, 0.58-1.23) in the low, medium, and high PRS group, respectively. Within any time interval, risks were lower for distal than for proximal CRCs. - Conclusions - Based on findings from a population-based case-control study, the recommended 10-year screening interval for colonoscopy may not need to be shortened among people with high PRSs, but could potentially be prolonged for people with low and medium PRSs. Studies are needed to address personalized time intervals for repeat colonoscopies in average-risk screening cohorts.